Spinal Endoscopy for Delayed-Onset Lumbar Radiculopathy Resulting from Foraminal Stenosis after Osteoporotic Vertebral Fracture: A Case Report of a New Surgical Strategy. (25th October 2018) - Ishimoto, Yuyu; Yamada, Hiroshi; Curtis, Elizabeth; Cooper, Cyrus; Hashizume, Hiroshi; Minamide, Akihito; Nakagawa, Yukihiro; Yoshida, Munehito
Abstract : There is little evidence regarding the optimal approach to treatment for delayed-onset lumbar radiculopathy due to foraminal stenosis after osteoporotic vertebral fracture. Here, we describe the use of spinal endoscopy for the treatment of this disabling condition, in an 80-year-old woman presenting with severe radicular pain following an osteoporotic lumbar compression fracture. Radiographic findings showed the compression of the L2 root within the foramen, and computed tomography identified a fragment of the posterior wall of the vertebral body under the pedicle. Since the patient had little back pain and was relatively frail, we decided to perform foraminal decompression via a lateral approach using spinal endoscopy. Intraoperative findings demonstrated degenerative changes as well as a fragment of the posterior wall of the fractured vertebral body in the foramen, covered in a fibrous film. The nerve was decompressed on removal of the fragment. After surgery, the patient experienced immediate pain relief. The preoperative Japanese Orthopedic Association (JOA) and visual analogue scale (VAS) scores were 9 and 82, respectively, and at 36-month follow-up, scores were reduced to 19 and 34, respectively.